2022
DOI: 10.31083/j.fbs1404029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Involvement of Potassium Channels in Fibromyalgia

Abstract: Fibromyalgia is a central sensitivity syndrome that presents with chronic pain, fatigue, cognitive dysfunction, and disordered sleep. The pathophysiology which due to multisensory hypersensitivity of the central nervous system involves neuronal excitability leading to central sensitization. Treatments of the challenges associated with the complexities of fibromyalgia involve combinations of pharmacological and non-pharmacological therapeutic approaches which often offer limited benefit. Potassium (K + ) channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…K channels are involved in fibromyalgia in FD/MAS, with channels including fast K + channels, potassium leak (KL) channels, KCHN2 voltage-gated potassium channels, and Kv channel autoantibodies. Additionally, it has been found that the water fraction of substance P (SP) is elevated in the cerebrospinal fluid of FD/MAS patients [ 63 ]. Substance P is a mediator of pain, is involved in pain production and transmission signaling, and can also exhibit anti-injury-sensing properties.…”
Section: Potassium Channel Involvement In Patients With Fd/masmentioning
confidence: 99%
“…K channels are involved in fibromyalgia in FD/MAS, with channels including fast K + channels, potassium leak (KL) channels, KCHN2 voltage-gated potassium channels, and Kv channel autoantibodies. Additionally, it has been found that the water fraction of substance P (SP) is elevated in the cerebrospinal fluid of FD/MAS patients [ 63 ]. Substance P is a mediator of pain, is involved in pain production and transmission signaling, and can also exhibit anti-injury-sensing properties.…”
Section: Potassium Channel Involvement In Patients With Fd/masmentioning
confidence: 99%